High-activity transition metal phosphide electrolyzed water catalyst and preparation method thereof
A multi-step process for preparing a transition metal phosphide catalyst with nitrogen and sulfur doping addresses the issues of high energy consumption and instability, enhancing catalytic performance and stability for water electrolysis.
Patent Information
- Application Number
- CN202510468012.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2025-07-15
AI Technical Summary
The existing transition metal phosphide catalysts have problems such as uneven distribution of active sites, poor stability and complex preparation process during the electrolysis process.
By adopting polymetallic phosphating-sulfide-plasma composite technology, by introducing precious metal dopants such as Ru and Ir, combined with phosphating, sulfating and plasma treatment, a high-active transition metal phosphide catalyst is formed to optimize the electronic structure and active site distribution.
The electrocatalytic activity and stability of the catalyst are improved, especially in the hydrogen evolution reaction, which shows excellent current density and stability, which solves the problems of low activity of traditional catalysts and uneven bubble precipitation, and improves the small current fluctuation and long-term service life.
Smart Images

Figure CN120311237A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst processing, and specifically to a highly active transition metal phosphide electrocatalyst for water electrolysis and a preparation method thereof. Background Art
[0002] With the transformation of the global energy structure and the promotion of the carbon neutrality goal, hydrogen energy, as an important carrier of clean energy, the innovation of its preparation technology has become increasingly important. Hydrogen production by water electrolysis has become a research hotspot in the field of hydrogen production due to its high efficiency and environmental friendliness. In this process, the performance of the catalyst directly affects the hydrogen production rate and energy efficiency. Therefore, the development of highly efficient and stable electrocatalysts for water electrolysis is of great significance for improving the efficiency of hydrogen energy production and reducing costs.
[0003] Currently, transition metal phosphides have become the focus of research on electrocatalysts for water electrolysis due to their excellent electrocatalytic performance. These materials exhibit low overpotentials and high current densities in the hydrogen evolution reaction (HER), showing good catalytic activity. In addition, transition metal phosphides have good stability and can maintain high catalytic performance during long-term electrochemical reactions.
[0004] Although transition metal phosphides have good stability and can maintain high catalytic performance during long-term electrochemical reactions, there are still some deficiencies in the practical application of existing multi-metal phosphide catalysts; firstly, traditional catalyst preparation methods often involve steps such as high-temperature calcination, which consume a large amount of energy and have high costs; secondly, the stability and durability of the catalyst still need to be improved. Especially during long-term water electrolysis reactions, the catalyst is prone to performance degradation; in addition, the uneven distribution of the conductivity and active sites of the catalyst also affects its catalytic performance. Summary of the Invention
[0005] Aiming at the deficiencies of the existing technology, the present invention provides a highly active transition metal phosphide electrocatalyst for water electrolysis and a preparation method thereof, which solves the problems of uneven distribution of active sites, poor stability, and complex preparation process in the existing technology.
[0006] To achieve the above objectives, the present invention is realized through the following technical solutions: A highly active transition metal phosphide electrocatalyst for water electrolysis, the catalyst comprising the following components in parts by weight:
[0007] Cobalt dichloride hexahydrate (CoCl2·6H2O): 1 - 3 parts, (manufacturer: AlfaAesar, CAS: C805641), which serves as the main metal source of the catalyst. Cobalt dichloride hexahydrate (CoCl2·6H2O) can form active phases such as Co-P and Co-S during subsequent phosphidation and sulfidation processes. Among them, the Co element has variable valences (Co 2+ / Co 3+) It is conducive to electron transfer and can effectively promote the adsorption and conversion of intermediate species during the hydrogen evolution and oxygen evolution processes. In addition, the d-orbital electron structure of cobalt endows it with excellent hydrogen adsorption and dissociation properties, which helps to improve the activity and reaction rate of the electrocatalytic reaction;
[0008] Ruthenium(III) chloride (RuCl3): 0.5 - 1.5 parts (manufacturer: Strem Chemicals, CAS: 96 - 1100). As a noble metal dopant, the introduction of Ru element can effectively reduce the overpotential of the hydrogen evolution reaction and promote the rapid conversion of H * (adsorbed hydrogen atom state). At the same time, the addition of Ru can adjust the electronic structure of the catalyst, optimize the surface energy band, make the electron density near the Co active site more reasonable, and thus promote the kinetic processes of HER and OER reactions. In addition, the high stability of Ru helps to improve the overall corrosion resistance and durability of the catalyst;
[0009] Iridium(III) chloride hydrate (IrCl3·xH2O): 0.5 - 1.5 parts (manufacturer: Alfa Aesar, CAS: 13385). As another noble metal dopant, the Ir element exhibits extremely high catalytic activity in the electrocatalytic OER reaction. The introduction of Ir not only helps to lower the energy barrier during the OER process, but also promotes the formation of high-valent Ir - O intermediates and improves the electron transfer efficiency during the water oxidation process. In addition, the formation of multi-metal composite active sites between Ir, Co, and Ru further enhances the reaction activity and stability of the catalyst;
[0010] Copper(II) sulfate pentahydrate (CuSO4·5H2O): 1 - 2 parts (manufacturer: Sigma - Aldrich, CAS: 7758 - 99 - 8). The addition of copper(II) sulfate pentahydrate can introduce Cu element into the catalyst material. The presence of Cu can improve the conductivity of the material and reduce the charge transfer resistance. At the same time, Cu can regulate the electron density and local environment on the catalyst surface, optimize the binding strength of the metal - hydrogen (M - H) bond, and further promote the HER reaction kinetics. In addition, the multi-valence characteristics of Cu help to construct more charge transfer channels and improve the overall electron transport efficiency;
[0011] Sodium hypophosphite (NaH2PO2): 2 - 4 parts (manufacturer: Alfa Aesar, CAS: 7681 - 53 - 0). Sodium hypophosphite, as a phosphorus source, plays a key role in the phosphidation treatment of the catalyst. Through heat treatment, sodium hypophosphite decomposes to generate active P atoms, which react with various metal elements (Co, Ru, Ir, Cu) to form metal phosphides (M - P, where M is a metal element). Metal phosphides have excellent catalytic activity and stability, and the P element can reduce H *The adsorption free energy is optimized, and the reaction path is promoted to facilitate the rapid evolution of gas during the HER and OER processes;
[0012] Urea (CO(NH2)2): 1 - 2 parts, (manufacturer: Sigma-Aldrich, CAS: 57-13-6) Urea serves as a nitrogen source and a carbon source, and decomposes into ammonia and carbonaceous substances during the heat treatment process. Among them, the doping of nitrogen elements can regulate the electronic structure of the catalyst, form N-doped carbon or M-N-C structures, and enhance the conductivity and activity of the catalyst. In addition, the presence of nitrogen can improve the hydrophilicity of the catalyst surface, improve the wettability of the electrolyte and the interface contact effect, and is conducive to the stable progress of the electrocatalytic reaction;
[0013] Glucose (C6H 12 O6): 1 - 2 parts, (manufacturer: Sigma-Aldrich, CAS: 50-99-7) Glucose serves as a carbon source and can form a carbon coating layer or carbon nanostructure under high-temperature treatment, effectively protecting the metal components of the catalyst and preventing the agglomeration and dissolution of metal particles. At the same time, the excellent conductivity of the carbon material can accelerate the electron transfer rate and improve the catalytic reaction efficiency. The presence of the carbon layer can also improve the hydrophobicity of the catalyst, promote the rapid release of the generated gas, and reduce the blockage of active sites;
[0014] Sodium sulfide nonahydrate (Na2S·9H2O): 1 - 2 parts, (manufacturer: Wuhan Jiyesheng Chemical Co., Ltd., CAS: 1313-84-4) Sodium sulfide nonahydrate serves as a sulfur source and can introduce S elements during the sulfidation modification process. The doping of S can regulate the surface electronic structure of the catalyst, optimize the binding ability of metal-hydrogen or metal-oxygen bonds, and promote the stability and rapid transformation of reaction intermediates. In addition, the presence of S can reduce the charge accumulation on the catalyst surface, improve the overall electronic regulation ability of the catalyst, and further enhance the bifunctional performance of HER and OER;
[0015] Aluminum chloride hexahydrate (AlCl3·6H2O): 0.5 - 1 part, (manufacturer: Jiangxi Pengteng Industry Co., Ltd., CAS: 7784-13-6) The introduction of aluminum chloride hexahydrate can provide Al 3+ ions, which play a role in stabilizing the skeleton in the structure of the catalyst. The high electronegativity of Al helps to improve the conductivity and structural strength of the material. At the same time, the presence of Al elements can effectively prevent the dissolution and structural collapse of the catalyst during the long-term reaction process, ensuring the stable operation of the catalyst;
[0016] Deionized water: 50 - 100 parts, Deionized water serves as a solvent and plays a good role in dissolution, dispersion and reaction medium during the preparation of the precursor. It ensures the full dissolution and uniform reaction of various metal salts, nitrogen sources, carbon sources, etc. in the solution, helps the formation of a homogeneous precursor, and improves the quality of subsequent heat treatment and phosphating reaction;
[0017] Cetyltrimethylammonium bromide (CTAB): 0.1 - 0.5 parts, (manufacturer: Sigma - Aldrich, CAS: 57 - 09 - 0) As a cationic cetyltrimethylammonium bromide, it can effectively regulate the morphology and dispersibility of particles during the formation of the catalyst precursor, prevent the aggregation and non - uniform growth of particles, promote the formation of regular nanostructures and a rich specific surface area, and thus provide more catalytic active sites and improve the overall catalytic performance.
[0018] The present invention also provides a method for preparing a highly active transition metal phosphide electro - catalytic water - splitting catalyst, comprising the following steps:
[0019] S1. Preparation of the precursor solution;
[0020] S2. Solvothermal reaction;
[0021] S3. Drying and calcination;
[0022] S4. Phosphidation treatment;
[0023] S5. Sulfidation modification;
[0024] S6. Plasma - assisted treatment.
[0025] Preferably, the preparation of the precursor solution includes:
[0026] Dissolve cobalt dichloride hexahydrate, ruthenium trichloride, iridium(III) hydrate chloride, and copper sulfate pentahydrate in deionized water, with a stirring speed of 300 - 500 rpm and a stirring time of 30 - 60 minutes to form a uniform metal ion solution. The aqueous solution environment promotes the full and uniform dispersion and dissolution of various metal ions, thus avoiding problems such as uneven distribution, aggregation, or clustering of metal ions during subsequent reaction processes. In particular, the synergistic effect of the cobalt, ruthenium, iridium, and copper multi - metal system requires good uniformity at the precursor stage. The control of the stirring speed and time within this range can accelerate the dissolution speed, ensure the stability of the system, and is beneficial to the uniformity of subsequent nucleation and crystal growth;
[0027] Urea and glucose are added to the metal ion solution as nitrogen and carbon sources to adjust the reducibility and pH value of the solution. On the one hand, urea can thermally decompose during subsequent solvothermal or calcination processes, releasing ammonia (NH3) and nitrogen species to achieve nitrogen doping and form M-N (metal-nitrogen) or C-N (carbon-nitrogen) active structures. These nitrogen-doped sites can effectively regulate the electronic structure of the catalyst, increase the electron density, improve the conductivity, and promote the stability of intermediate states in HER and OER. On the other hand, glucose, as an excellent carbon source, can not only carbonize to form carbon coatings or carbon skeletons during subsequent heat treatment processes to improve the electron transport performance of the material, but also act as a reducing agent to regulate the reducibility of the system and promote the reduction deposition of some metal ions. In addition, the addition of glucose can fine-tune the pH value of the system, provide a suitable environment for the good deposition and complexation reactions of metal ions, inhibit the rapid hydrolysis or precipitation of metal ions, and ensure the uniformity and stability of the precursor;
[0028] Crystalline aluminum chloride is added to provide the alumina component and enhance the structural stability of the catalyst. The main purpose of adding crystalline aluminum chloride is to generate well-dispersed Al species through its hydrolysis and complexation reactions in the solution. These Al species can be embedded or coated in the multi-metal precursor structure during subsequent reaction processes, and then form an Al-O skeleton or Al-doped sites during calcination and phosphidation processes. The presence of Al not only helps to improve the mechanical strength and corrosion resistance of the catalyst and prevent structural collapse under long-term reactions, but also the electronegativity of Al 3+ can regulate the electronic environment on the surface of the catalyst, optimize the electron density of the metal active center, and enhance the overall catalytic activity;
[0029] Cetyltrimethylammonium bromide is added to control the morphology and dispersion of the precursor. CTAB belongs to cationic cetyltrimethylammonium bromide. Its molecular structure characteristics enable it to form an adsorption layer on the surface of metal ions or initially formed precursor particles through self-assembly in the solution, effectively inhibiting the excessive growth or aggregation of particles and promoting the uniform dispersion of particles. In addition, the addition of CTAB can induce the directional growth of the precursor, which is beneficial to constructing nanostructures with specific morphologies (such as nanosheets, nanorods, nanoflowers, etc.), further increasing the specific surface area of the material and exposing more active sites, providing a favorable morphological basis for subsequent catalytic reactions.
[0030] Preferably, the solvothermal reaction includes:
[0031] Transfer the precursor solution to a high-pressure reaction kettle. The design of the closed reaction kettle provides a high-temperature and high-pressure environment, which helps to increase the migration rate and diffusion rate of metal ions, thereby accelerating various metal ions (Co 2+ 、Ru 3+ 、Ir 3+ 、Cu 2+) The interaction between them promotes the uniform nucleation and assembly of the polymetallic precursor. In addition, components such as nitrogen source, carbon source, phosphorus source, and surfactant introduced into the precursor solution will also undergo physical or chemical reactions under this condition, providing a good growth environment for the formation of the multi-element composite precursor;
[0032] React at 160 - 200 °C for 12 - 24 hours, and the reaction pressure is 1.5 - 3 MPa to promote the formation of the precursor. Within this temperature range, the solvothermal condition can effectively induce hydrolysis, condensation, and complexation reactions of metal ions in the solution, which is beneficial to the co-deposition of multi-metal elements such as Co, Ru, Ir, Cu, etc., and form a uniformly distributed polymetallic hydroxide, phosphate, hydroxyphosphide, or composite precursor. The regulation of the reaction pressure can further limit the formation of bubbles and the disordered aggregation of particles, ensuring the compactness and uniformity of the precursor; meanwhile, in this high-temperature and high-pressure environment, the nitrogen source (urea) and carbon source (glucose) can be partially cracked to release gases such as ammonia (NH3) and carbon dioxide (CO2), promoting the formation of N-doped or C-doped precursor substances on the surface of the precursor, laying a good nitrogen-carbon environment for subsequent calcination and phosphating treatment;
[0033] After the reaction is completed, naturally cool to room temperature, take out the product for subsequent treatment. The control of the natural cooling process helps to reduce the stress accumulation inside the material, prevent structural defects or particle cracking caused by rapid cooling, and ensure the integrity and structural stability of the precursor.
[0034] Preferably, the drying and calcination include:
[0035] Wash the reaction product with deionized water 3 - 5 times, and the washing time for each time is 10 - 15 minutes. The main function of this washing step is to remove the impurity components on the surface of the precursor, especially unreacted chloride ions (Cl - ) and sulfate ions (SO4 2- ), as well as organic residues (residues of CTAB, glucose, or urea), etc. The presence of these impurities may not only decompose to produce harmful gases or form unstable substances during subsequent calcination but also affect the structural purity and electrocatalytic performance of the catalyst. Multiple washings can ensure the purity of the reaction product and enable it to form a polymetallic oxide precursor with uniform structure and stable composition during calcination, laying a good foundation for subsequent phosphating reaction;
[0036] Dry for 12 - 16 hours at 80 - 100 °C. The drying temperature and time within this range help to slowly and evenly evaporate the moisture remaining in the pores or on the surface of the precursor, preventing the accumulation of internal stress or structural damage in the particles due to rapid dehydration. In addition, the fully dried material can effectively avoid the explosive escape of water vapor during the subsequent high-temperature calcination process, improve the integrity and densification of the particles, and ensure the final formation of an oxide precursor structure with uniform distribution and controllable particle size;
[0037] Conduct calcination in argon or nitrogen, with the temperature range of 400 - 600 °C and the time of 2 - 4 hours to form a metal oxide precursor. In the high-temperature environment of 400 - 600 °C, the organic substances (from glucose, urea, or CTAB) inside the material undergo pyrolysis or carbonization reactions, partially forming nitrogen-doped carbon (N-C) or a carbon coating layer, and releasing gases simultaneously to promote the formation of the pore structure. In addition, Co 2+ 、Ru 3+ 、Ir 3+ 、Cu 2+ and other multi-metal ions undergo hydrolysis condensation and oxidative recombination during calcination to generate multi-metal oxides with specific structures and stabilities (such as Co3O4, RuO2, IrO2, CuO, etc.); the protective atmosphere of argon or nitrogen can effectively inhibit the further oxidation of metal ions to unfavorable high valence states, ensuring the structural rationality and compositional homogeneity of the oxide precursor. In addition, this environment helps to retain the existence of some low-valence metals or active heteroatoms, providing a controllable reduction-phosphidation reaction environment for the subsequent phosphidation reaction and ensuring the uniformity and completeness of the phosphidation process.
[0038] Preferably, the phosphidation treatment includes:
[0039] Ball-mill and mix the calcined precursor with sodium hypophosphite in a ball mill at a speed of 250 - 350 rpm for 25 - 35 minutes. By utilizing the efficient mixing and shearing effects of mechanical ball milling, the particle surfaces of the metal oxide precursor and the sodium hypophosphite particles are fully contacted, enhancing their interfacial reaction activity during the subsequent heat treatment process. The ball milling process can not only break up larger particles, reduce the particle size, and increase the specific surface area, but also introduce surface defects and active sites to a certain extent, increasing the reactivity of the catalyst material. In addition, the uniformly dispersed NaH2PO2 decomposes upon heating during the temperature rise, releasing active phosphidation gases (PH3 or P species), enabling the phosphorus source to act more uniformly on the surface and inside of the precursor and promoting the comprehensive progress of the metal phosphidation reaction;
[0040] Low-temperature pre-phosphating is performed at 300-350°C for 1-2 hours. The purpose of low-temperature pre-phosphating is to control the reaction to proceed slowly and avoid the instantaneous decomposition of phosphorus sources at high temperatures, which may cause uneven phosphating or structural damage. Under the temperature conditions of 300-350°C, sodium hypophosphite will slowly decompose to release PH3 gas or other active phosphorus species. These active phosphorus atoms can preferentially react with metal ions (Co, Ru, Ir, Cu, etc.) on the surface of the precursor to generate preliminary metal phosphides (such as Co-P, Ru-P, Ir-P, etc.) or form a phosphorus coating layer, laying the foundation for subsequent deep phosphating and structural regulation. At the same time, this process can also effectively promote the further removal of residual organic matter and improve the purity of the material;
[0041] Then the temperature is raised to 600-700℃ for high-temperature rephosphating for 2-3 hours to form a metal phosphide with high crystallinity. By raising the temperature to 600-700℃, the release rate of PH3 or active P species can be accelerated, so that the phosphorus source can diffuse quickly into the interior of the precursor, and at the same time, the metal elements (Co, Ru, Ir, Cu) are fully combined with phosphorus to form a stable metal-phosphorus (MP) bond. In addition, the high temperature environment can drive the grain growth and crystal reconstruction of the phosphating product, improve its crystallinity and structural integrity, and help form a stable metal phosphide phase (such as CoP, RuP2, IrP2, Cu3P, etc.); at the same time, the high temperature phosphating process can also promote the stable embedding or combination of doping elements (such as N, C, S, etc.) in the metal phosphide matrix, further optimize the electronic structure and surface chemical environment of the material, and improve its conductivity and exposure of active sites in the electrocatalytic reaction.
[0042] Preferably, the sulfurization modification includes:
[0043] The phosphating product is immersed in a sodium sulfide nonahydrate solution, wherein the concentration of the sodium sulfide nonahydrate solution is 0.1-0.5 mol / L, and the sodium sulfide nonahydrate can dissociate a large amount of S in the solution. 2- and HS - Ions, these active sulfur ions can effectively chemically combine or physically adsorb with the unsaturated metal sites (Co, Ru, Ir, Cu, etc.) on the surface of metal phosphides to form metal-sulfur (MS) bonds, further regulating the surface electronic structure of the catalyst. The introduction of S elements helps to reduce the hydrogen adsorption free energy (ΔG_H * ), improve HER activity, improve the electron cloud distribution of the catalyst, and promote the stability of the intermediate state during the OER reaction. In addition, S doping can also induce the formation of more active defects and boundary sites on the catalyst surface, improving the overall reaction kinetics;
[0044] React at 60 - 80 °C for 2 - 4 hours, with a stirring speed of 200 - 400 rpm during this period to promote the adsorption and diffusion of sulfide ions. The reaction temperature in this range (60 - 80 °C) can accelerate the binding rate of S 2- with the metal sites, promote the deep progress of the sulfidation reaction, and avoid the destruction of the catalyst structure under high-temperature conditions. The continuous stirring not only facilitates the uniform diffusion of active sulfide ions to the surface and inner pores of the catalyst particles but also effectively prevents the agglomeration between particles, ensuring the uniformity of sulfidation modification. This process further promotes the formation of a sulfur / phosphorus / metal heterogeneous interface on the surface of metal phosphides, helps to construct cooperative catalytic active sites, and improves the comprehensive performance of the catalyst;
[0045] After the reaction is completed, take out the product and wash it 3 - 5 times with deionized water, each time for 10 - 15 minutes, to remove the unbound sulfides on the surface. The purpose of multiple deionized water washes is to thoroughly remove the unbound Na2S residues and free S 2- ions, preventing their precipitation or migration during subsequent applications and affecting the stability of the catalyst and the stability of the reaction environment. In addition, this step can further remove the by-products or free ions that may be generated during the sulfidation reaction, ensuring that the electrochemical reaction activity of the catalyst material is not interfered with;
[0046] Then dry it in a vacuum drying oven at 80 - 100 °C for 8 - 12 hours to obtain a sulfur-rich structured phosphide catalyst. The purpose of low-temperature vacuum drying is to thoroughly remove moisture on the premise of ensuring that the material structure is not damaged, preventing the shielding of active sites or corrosion problems during long-term use caused by moisture residue. In addition, the vacuum environment can also prevent oxygen or impurities in the air from entering the material surface, maintaining its fresh and active M - S binding state and rich sulfur-doped structure.
[0047] Preferably, the plasma-assisted treatment includes:
[0048] Perform nitrogen plasma treatment on the phosphidation product in a plasma reaction chamber. Among them, the gas flow rate is set to 50 - 100 sccm, the plasma power is 100 - 200 W, and the treatment time is 5 - 10 minutes. The establishment of the nitrogen plasma environment is mainly to ionize, excite, or decompose inert nitrogen gas (N2) using high-energy plasma technology to form active nitrogen radicals (N·), nitrogen ions (N +)), nitrogen chemical species (NH_x), etc. These reactive nitrogen species can react with unsaturated metal sites, metal-phosphorus bonds (M-P), or metal-sulfur bonds (M-S) on the catalyst surface to achieve surface nitridation, nitrogen doping, or nitrogen modification effects; with a power between 100 - 200 W, it can effectively excite nitrogen gas to form reactive nitrogen species, while avoiding surface etching or particle structure damage of the catalyst caused by excessive energy. Treatment for a relatively short time (5 - 10 minutes) helps to quickly form a thin nitrogen-doped region or surface nitrogen modification layer, while retaining the advantageous structures of the original metal phosphide and sulfur doping. The introduction of reactive nitrogen species can further reduce the hydrogen adsorption free energy (ΔG_H * ) of the catalyst active center, enhancing the kinetic rate of the HER reaction; at the same time, it can optimize the adsorption energy of intermediate species (OH * , O * , OOH * ) during the OER process, improving the overall bifunctional electrocatalytic performance;
[0049] The pressure in the reaction chamber is controlled at 10 - 50 Pa, and after the treatment, the catalyst is naturally cooled to room temperature and stored in a sealed manner. The low-pressure (10 - 50 Pa) reaction environment helps to improve the stability of nitrogen plasma and the migration rate of reactive nitrogen species, while preventing the rapid annihilation of reactive species under high-pressure conditions; natural cooling can avoid the generation of thermal stress or structural rupture of the catalyst due to rapid cooling, while maintaining the integrity and stability of the nitrogen-doped surface. The operation of sealed storage is to prevent oxygen or water vapor in the air from reacting with the freshly exposed reactive nitrogen / metal sites of the catalyst, causing surface activity loss or the formation of unstable phases, ensuring the high efficiency and long-term stability of the material in subsequent electrocatalytic applications.
[0050] The present invention provides a high-activity transition metal phosphide electrocatalyst for water electrolysis and a preparation method thereof.
[0051] It has the following beneficial effects:
[0052] 1. The present invention adopts a multi-metal phosphidation-sulfidation-plasma composite technology to improve the electrocatalytic activity of the catalyst, especially showing excellent current density and stability in the hydrogen evolution reaction. Compared with the prior art, the present invention successfully solves the problems of low activity and uneven bubble evolution of traditional catalysts through the synergistic effect of introducing nitrogen plasma doping and metal phosphide, making the catalyst more efficient in an acidic environment, with smaller current fluctuations and greatly improved stability.
[0053] 2. The plasma-assisted treatment technology of the present invention optimizes the electronic structure of the catalyst by introducing nitrogen elements, forms stable M-N bond sites, and induces more boundary defects and amorphous structure sites. These regions effectively accelerate the conversion of reaction intermediates and the electron transport process. Compared with traditional catalysts, the present invention solves the problem of lack of surface active sites and improves the rate and efficiency of catalytic reactions.
[0054] 3. The catalyst of the present invention exhibits excellent electrochemical stability. In the continuous current density test, only a small potential drift occurs, and no obvious peeling phenomenon is observed in the catalytic layer. This stability stems from the unique nitrogen plasma doping structure, which avoids the problems of activity decay and material shedding of traditional catalysts during long-term use. Compared with the catalysts in the prior art, the catalyst of the present invention can better maintain the integrity of its structure and stable current output, and improves its long-term service life.
[0055] 4. The multi-metal phosphidation-sulfidation-plasma composite strategy adopted by the present invention optimizes the dual catalytic performance of the catalyst in hydrogen evolution and oxygen evolution reactions. Compared with the single phosphidation or sulfidation method in the prior art, the present invention effectively solves the problems of low catalytic activity and poor selectivity in bifunctional catalysts, provides a highly efficient and stable water decomposition catalyst, and greatly promotes the practical application of water decomposition technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is a flowchart of the preparation method of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0057] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the drawings in the specification of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0058] Please refer to the attached Figure 1 :
[0059] Example 1:
[0060] Raw material ratio (parts by weight):
[0061] Cobalt dichloride hexahydrate: 3 parts; Ruthenium trichloride: 0.5 part; Iridium(III) chloride hydrate: 0.5 part; Copper sulfate pentahydrate: 1 part; Sodium hypophosphite: 4 parts; Urea: 2 parts; Glucose: 1 part; Sodium sulfide nonahydrate: 2 parts; Crystalline aluminum chloride: 1 part; Cetyltrimethylammonium bromide: 0.5 part; Deionized water: 100 parts.
[0062] Step description:
[0063] Preparation of S1 precursor solution: Dissolve all metal salts in 100 parts of deionized water, with a stirring rate of 500 rpm and a stirring time of 60 minutes. Add urea and glucose, and then add crystalline aluminum chloride and the surface modifier CTAB.
[0064] S2 solvothermal reaction: Transfer to a high-pressure reactor and react at 200 °C and 3 MPa for 24 hours, then cool naturally to room temperature.
[0065] S3 drying and calcination: Wash 4 times, 15 minutes each time, dry at 80 °C for 14 hours; then calcine in an argon atmosphere at 600 °C for 3 hours to obtain the metal oxide precursor.
[0066] S4 phosphating treatment: Mix the precursor with 4 parts of sodium hypophosphite in a ball mill at 300 rpm for 30 minutes; pre-phosphatize at 320 °C for 1.5 hours first, and then perform high-temperature phosphating at 650 °C for 2.5 hours to form the metal phosphide.
[0067] S5 sulfidation modification: Immerse the product in a 0.3 mol / L sodium sulfide nonahydrate solution, react at 70 °C for 3 hours, with a stirring speed of 300 rpm; wash 5 times and then dry in vacuo at 90 °C for 10 hours.
[0068] S6 plasma treatment: In the plasma reaction chamber, treat at a nitrogen flow rate of 50 sccm, a power of 150 W, for 5 minutes, with a chamber pressure of 30 Pa, and then seal and store after natural cooling.
[0069] Example 2:
[0070] Raw material ratio (parts by weight):
[0071] Cobalt dichloride hexahydrate: 1 part; Ruthenium trichloride: 1 part; Iridium(III) chloride hydrate: 1 part; Copper sulfate pentahydrate: 2 parts; Sodium hypophosphite: 3 parts; Urea: 1 part; Glucose: 2 parts; Sodium sulfide nonahydrate: 1 part; Crystalline aluminum chloride: 0.5 part; Cetyltrimethylammonium bromide: 0.2 part; Deionized water: 80 parts.
[0072] Step description:
[0073] S1 precursor solution preparation: Dissolve all metal salts in 80 parts of deionized water, with a stirring rate of 400 rpm and a stirring time of 45 minutes, and add urea, glucose, crystalline aluminum chloride and CTAB.
[0074] S2 solvothermal reaction: React at 180 °C and 2 MPa for 18 hours, then cool naturally to room temperature.
[0075] S3 Drying and Calcination: The product was washed with water three times, 10 minutes each time, dried at 90 °C for 12 hours; calcined at 500 °C for 4 hours under nitrogen.
[0076] S4 Phosphating Treatment: Ball-milled with 3 parts of sodium hypophosphite (350 rpm) for 35 minutes; pre-phosphated at 300 °C for 2 hours, and then phosphated at 700 °C for 3 hours.
[0077] S5 Sulfuration Modification: Reacted in 0.1 mol / L sodium sulfide solution at 60 °C for 2 hours, stirring speed 250 rpm; washed with water three times, dried at 80 °C for 12 hours.
[0078] S6 Plasma Treatment: The treatment conditions were nitrogen flow rate 100 sccm, power 200 W, treatment for 10 minutes, chamber pressure 50 Pa, and stored sealed after cooling.
[0079] Example 3:
[0080] Raw Material Ratio (parts by weight):
[0081] Cobalt Dichloride Hexahydrate: 2 parts; Ruthenium Trichloride: 1.5 parts; Iridium(III) Chloride Hydrate: 1.5 parts; Copper Sulfate Pentahydrate: 1.5 parts; Sodium Hypophosphite: 2 parts; Urea: 1 part; Glucose: 1 part; Sodium Sulfide Nonahydrate: 1.5 parts; Aluminum Chloride Hexahydrate: 0.8 part; Cetyltrimethylammonium Bromide: 0.3 part; Deionized Water: 90 parts.
[0082] Step Description:
[0083] S1 Preparation of Precursor Solution: All metal salts were dissolved in 90 parts of deionized water, stirring speed 350 rpm, for 40 minutes, and then the auxiliary agent and surface modifier were added.
[0084] S2 Solvothermal Reaction: Reacted at 160 °C and 1.5 MPa for 12 hours, cooled to room temperature.
[0085] S3 Drying and Calcination: The product was washed 3 times, 15 minutes each time, dried at 100 °C for 16 hours; calcined at 550 °C for 3 hours under nitrogen.
[0086] S4 Phosphating Treatment: Ball-milled with 2 parts of sodium hypophosphite (250 rpm) for 25 minutes; pre-phosphated at 310 °C for 1 hour, and then treated at 600 °C for 2 hours.
[0087] S5 Sulfuration Modification: Immersed in 0.5 mol / L sodium sulfide nonahydrate solution, reacted at 80 °C for 4 hours, stirred at 400 rpm, washed 5 times and dried at 100 °C for 8 hours.
[0088] S6 Plasma Treatment: Adopted nitrogen flow rate 75 sccm, power 180 W, time 7 minutes, pressure controlled at 40 Pa, cooled to room temperature and stored sealed.
[0089] Comparative Example 1: Compared with Example 1, the difference lies in that the ruthenium trichloride component is not added, and the rest are the same.
[0090] Comparative Example 2: Compared with Example 1, the difference lies in that the nitrogen plasma-assisted treatment is not carried out, and the rest are the same.
[0091] Comparative Example 3: Compared with Example 2, the difference lies in that sodium sulfide nonahydrate is replaced with thiourea as the sulfur source, and the rest are the same.
[0092] Comparative Example 4: Compared with Example 2, the difference lies in that the high-temperature phosphating temperature in the phosphating treatment is 750 °C, and the rest are the same.
[0093] Comparative Example 5: Compared with Example 3, the difference lies in that the glucose component is not added to the precursor solution, and the rest are the same.
[0094] Comparative Example 6: Compared with Example 3, the difference lies in that the plasma treatment pressure is set to 80 Pa, and the rest are the same.
[0095] Test Example 1:
[0096] Experimental purpose: To evaluate the stable current output ability of different catalyst samples under fixed potential conditions, and to reflect their catalytic activity levels for the hydrogen evolution reaction in the electrolysis of water in an acidic environment.
[0097] Overview of experimental principle: In the electrocatalytic reaction, a representative hydrogen evolution potential (for example, -0.25 V vs RHE) is fixed, and the steady-state current density generated by the catalyst electrode at this potential is measured (the current value per unit area, mA / cm 2 ), which can intuitively reflect its catalytic efficiency. The higher the current density, the more hydrogen is generated per unit time, and the stronger the catalytic performance.
[0098] Experimental steps:
[0099] Sample preparation:
[0100] Each catalyst sample was ultrasonically dispersed in an isopropanol + Nafion mixture to form a catalyst ink. 20 μL was taken and evenly drop-coated on the surface of a Φ5 mm glassy carbon electrode and dried at room temperature to form a film.
[0101] Electrochemical test system:
[0102] Electrolyte: 0.5 M H2SO4;
[0103] Three-electrode system:
[0104] Working electrode: Glassy carbon sheet loaded with catalyst;
[0105] Counter electrode: Platinum sheet;
[0106] Reference electrode: Ag / AgCl (saturated KCl);
[0107] Electrochemical workstation: potentiostatic mode (chronoamperometry).
[0108] Test procedure:
[0109] Operate at a constant potential of -0.25 V (vs RHE) for 300 seconds;
[0110] Record the instantaneous current density every 30 seconds, and calculate the average steady-state current density within the last 30 seconds, with the unit of mA / cm 2 ;
[0111] Record the surface stability of the sample and the bubble evolution rate as auxiliary characterizations.
[0112] Sample number description: Examples 1, 2, 3, Comparative Example 1, Comparative Example 2, Comparative Example 5 (experimental results are shown in Table 1).
[0113] Table 1: Comparison results of current density at a fixed potential (-0.25 V vs RHE)
[0114]
[0115] It can be seen from Table 1 that:
[0116] First of all, the high HER current density in Example 1 benefits from the multi-metal phosphide structure formed by metals such as Ru, Co, and Cu. The introduction of Ru effectively regulates the electron distribution of the metal center, making it have a more suitable hydrogen adsorption free energy (ΔG_H * ). After the absence of Ru in Comparative Example 1, the electron synergy of the active center is significantly reduced, resulting in the inability to effectively convert the surface-adsorbed hydrogen into molecular hydrogen, and the hydrogen evolution activity decreases. The experimental data is highly consistent with the theoretical deduction.
[0117] Furthermore, the plasma-assisted treatment plays a key role in Examples 1-3. Especially in Example 1, the formed N-doped environment can stabilize the surface electron states and induce more boundary defects and amorphous structure sites, which helps to accelerate the transformation of catalytic reaction intermediates and the electron transfer process. After the lack of plasma treatment in Comparative Example 2, it is manifested as slow bubble release and large current fluctuations, indicating that the surface stability and charge migration ability of the catalyst are significantly reduced after the absence of active nitrogen species, further confirming the importance of nitrogen plasma for the regulation of the surface and interface energy band structure.
[0118] In addition, glucose, as a reducing carbon source, participates in controlling the crystal growth environment and precursor structural homogeneity during the synthesis of the precursor. In the embodiment, it and urea together create a reduction and pH-stable growth condition, which is conducive to the formation of a highly crystalline and uniformly dispersed metal phosphide complex during the subsequent phosphating and sulfiding processes. After the lack of glucose in comparative example 5, the catalyst electrode deposition was uneven and local shedding was more obvious, and the current density decreased, reflecting the degradation of the material structure integrity and electronic conductivity. This phenomenon echoes the action path of "carbon source assisted nucleation and morphology regulation" proposed in the previous mechanism analysis, and strengthens the scientific basis and engineering feasibility of the material design idea of the present invention.
[0119] Test Example 2:
[0120] Experimental purpose: To compare the oxygen evolution performance of different catalysts under alkaline conditions and their overall water splitting efficiency in a dual-electrode system, and to verify the effectiveness of a reasonable multi-metal phosphating-sulfiding-plasma composite strategy in improving the performance of dual-functional catalysis.
[0121] Experimental system and condition settings:
[0122] 1. Electrocatalytic oxygen evolution performance test (OER):
[0123] Electrolyte: 1.0M KOH;
[0124] Three-electrode system:
[0125] Working electrode: catalyst glassy carbon sheet;
[0126] Reference electrode: Hg / HgO (1.0MKOH);
[0127] Counter electrode: platinum sheet.
[0128] Test method:
[0129] At a fixed current density (10 mA cm -2 ) to record the desired potential (η@10mA);
[0130] The test lasted for 300 seconds and the steady-state voltage was recorded.
[0131] 2. Overall water decomposition test (full water decomposition performance):
[0132] System: double-electrode symmetrical electrolyzer;
[0133] The same catalyst is used for both positive and negative electrodes;
[0134] Electrolyte: 1.0M KOH.
[0135] Operating parameters:
[0136] The overall cell voltage required at 10 mA·cm -2 ;
[0137] Apply continuous power for 10 minutes and monitor the voltage fluctuation;
[0138] Record the oxygen evolution and hydrogen evolution bubble conditions and the degree of polarization.
[0139] Sample numbers; Examples 1, 2, 3, Comparative Example 3, Comparative Example 4, and Comparative Example 6 (experimental results are shown in Table 2).
[0140] Table 2: Comparison table of OER performance and overall water splitting performance
[0141]
[0142] It can be seen from Table 2 that:
[0143] From a mechanistic perspective, the heterostructure formed by the phosphidation of noble metals such as Ru and Ir with multi-metals such as Co and Cu provides abundant high-valent metal active centers in the alkaline oxygen evolution reaction, promoting the stable adsorption and rapid dissociation of intermediate states ( * OH, * O, * OOH). Among them, the formed M-P bond after phosphidation treatment helps to regulate the metal electron cloud density, making it easier to achieve electron-proton co-transfer in the reaction path. This is the key reason for the lower OER onset potential of the example samples.
[0144] On this basis, the introduction of sulfurization modification further strengthens the surface electron structure perturbation of metal sites. The introduction of S 2- not only constructs M-S / M-P boundary sites but also induces the formation of surface defects and high-energy state structures. These regions become the centers of charge aggregation and reaction acceleration during the OER process. In Comparative Example 3, when sodium sulfide nonahydrate was replaced with thiourea, due to the insufficient release rate of active sulfur species, a stable sulfur-doped layer could not be formed, resulting in a significant reduction in effective active sites in the overall structure, and thus a decrease in catalytic efficiency.
[0145] In addition, plasma-assisted treatment further optimizes the conductivity and stability of the material by constructing a nitrogen-doped environment. Especially in the multi-metal cooperative system, after nitrogen atoms replace some surface anion positions, the d-orbital filling state can be adjusted, thereby increasing the adsorption / dissociation rate of intermediate species. In Comparative Example 6, due to the processing chamber pressure exceeding the reasonable range, the plasma was uneven and the doped layer had serious defects, showing obvious voltage fluctuations and polarization instability problems. This experimental phenomenon is consistent with the inference of "activity decay caused by failed surface energy band optimization" described in the mechanism analysis, further indicating that the plasma control parameters have a decisive impact on the final catalytic performance.
[0146] Test Example 3:
[0147] Experimental purpose: To verify the influence of different preparation processes on the current retention ability and structural stability of the catalyst during long-term electrochemical operation, to investigate the contributions of doping, crystal phase stability, and surface engineering to the durability performance, and to highlight the advantages of the strategy of the present invention in improving the service life of the catalyst.
[0148] Experimental system and test conditions:
[0149] I. Electrochemical stability test (Chronopotentiometry):
[0150] Electrolyte: 1.0 M KOH;
[0151] Three-electrode system:
[0152] Working electrode: Catalyst glassy carbon sheet;
[0153] Reference electrode: Hg / HgO (1.0 M KOH);
[0154] Counter electrode: Pt sheet.
[0155] Test mode:
[0156] Under the condition of a fixed current density of 10 mA·cm -2 Continuous power-on for 24 hours;
[0157] Record the stability of the voltage and observe the potential drift amplitude (unit: mV);
[0158] Express the degree of stability deterioration by the difference between the initial voltage and the end voltage.
[0159] II. Post-treatment structure analysis:
[0160] Analysis method:
[0161] Observe the visible changes of the catalyst film (such as shedding, discoloration, etc.);
[0162] Test the conductivity of the leaching solution to judge the dissolution of metal ions.
[0163] Sample number:
[0164] Example 2, Example 3, Comparative Example 2, Comparative Example 6 (experimental results are shown in Table 3).
[0165] Table 3: Comparative test results of electrocatalytic stability (constant current for 24 h)
[0166]
[0167]
[0168] From Table 3, we can get:
[0169] In Examples 2 and 3, the catalyst was -2 Only 20-30mV potential drift occurs under current density, and there is no obvious peeling of the electrode surface, indicating that the material structure is stable and the charge transfer path is continuously effective. This stability is due to the surface defects and heterogeneous bonding layers formed by nitrogen plasma doping mentioned in the previous mechanism. These structures not only increase the density of active sites, but also give the catalyst layer excellent interface adhesion and electrochemical corrosion resistance.
[0170] In Comparative Example 2, although the sample that has not been treated with plasma has good initial activity, it exhibits drastic potential drift and surface peeling during continuous power-on. In the absence of nitrogen doping stability, the catalytic layer is more susceptible to damage from local electric field stress and bubble impact, resulting in increased surface desorption and internal migration, forming a repeated passivation / reactivation cycle, which causes large fluctuations in potential. Mechanistically, this also confirms the key role of plasma treatment in constructing high-stability MN bonds and improving the uniformity of electronic structure, and is an indispensable process step for maintaining long-term electrocatalytic behavior.
[0171] In addition, in Comparative Example 6, although plasma treatment was performed, due to abnormal pressure control in the reaction chamber (80Pa, exceeding the recommended range), the doping layer was unevenly distributed, local peeling occurred in the surface stress concentration area, and slight leaching behavior was observed in the test. The increase in conductivity in the table reflects the migration of some metal components, which is consistent with the prediction of "high-energy uneven plasma environment destroys surface integrity" in the aforementioned mechanism.
[0172] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-activity transition metal phosphide electrocatalyst for water electrolysis, characterized in that, The catalyst comprises the following components in parts by weight: Cobalt dichloride hexahydrate: 1 - 3 parts; Ruthenium trichloride: 0.5 - 1.5 parts; Iridium(III) chloride hydrate: 0.5 - 1.5 parts; Copper sulfate pentahydrate: 1 - 2 parts; Sodium hypophosphite: 2 - 4 parts; Urea: 1 - 2 parts; Glucose: 1 - 2 parts; Sodium sulfide nonahydrate: 1 - 2 parts; Aluminum chloride hexahydrate: 0.5 - 1 part; Deionized water: 50 - 100 parts; Cetyltrimethylammonium bromide: 0.1 - 0.5 part.
2. A preparation method of a high-activity transition metal phosphide electrocatalyst for water electrolysis, characterized in that, Using a highly active transition metal phosphide electrolytic water catalyst as described in claim 1, comprising the following steps: S1. Preparation of the precursor solution; S2. Solvothermal reaction; S3. Drying and calcination; S4. Phosphating treatment; S5. Sulfurization modification; S6. Plasma-assisted treatment.
3. The preparation method of a highly active transition metal phosphide electrolytic water catalyst according to claim 2, wherein The preparation of the precursor solution includes: Dissolving cobalt dichloride hexahydrate, ruthenium trichloride, iridium(III) chloride hydrate, and copper sulfate pentahydrate in deionized water, with a stirring speed of 300 - 500 rpm and a stirring time of 30 - 60 minutes to form a uniform metal ion solution; Adding urea and glucose to the metal ion solution as a nitrogen source and a carbon source to adjust the reducibility and pH value of the solution; Adding aluminum chloride hexahydrate to provide alumina components and enhance the structural stability of the catalyst; Adding cetyltrimethylammonium bromide to control the morphology and dispersibility of the precursor.
4. The preparation method of a highly active transition metal phosphide electrolytic water catalyst according to claim 2, characterized in that, The solvothermal reaction includes: Transferring the precursor solution to a high-pressure reaction kettle; Reacting at 160 - 200 °C for 12 - 24 hours, with a reaction pressure of 1.5 - 3 MPa to promote the formation of the precursor; After the reaction is completed, naturally cool to room temperature and take out the product for subsequent treatment.
5. The preparation method of a highly active transition metal phosphide electrolytic water catalyst according to claim 2, wherein The drying and calcination include: Washing the reaction product with deionized water 3 - 5 times, with each washing time being 10 - 15 minutes; Drying at 80 - 100 °C for 12 - 16 hours; Conducting calcination in argon or nitrogen, with a temperature range of 400 - 600 °C and a time of 2 - 4 hours to form a metal oxide precursor.
6. The preparation method of a highly active transition metal phosphide electrolytic water catalyst according to claim 2, wherein The phosphating treatment includes: Ball-milling and mixing the calcined precursor and sodium hypophosphite in a ball mill at a speed of 250 - 350 rpm for 25 - 35 minutes; Performing low-temperature pre-phosphating at 300 - 350 °C for 1 - 2 hours; Subsequently, raising the temperature to 600 - 700 °C for high-temperature re-phosphating for 2 - 3 hours to form a highly crystalline metal phosphide.
7. The preparation method of a high-activity transition metal phosphide electrolytic water catalyst according to claim 2, characterized in that, The sulfurization modification includes: Soaking the phosphated product in a sodium sulfide nonahydrate solution with a solution concentration of 0.1 - 0.5 mol / L; Reacting at 60 - 80 °C for 2 - 4 hours, with a stirring speed of 200 - 400 rpm during the period to promote the adsorption and diffusion of sulfide ions; After the reaction is completed, taking out the product and washing it with deionized water 3 - 5 times, with each washing for 10 - 15 minutes to remove the unbound sulfide on the surface; Then drying in a vacuum drying oven at 80 - 100 °C for 8 - 12 hours to obtain a sulfur-rich structure phosphide catalyst.
8. The preparation method of a highly active transition metal phosphide electrolyzed water catalyst according to claim 2, characterized in that, The plasma-assisted treatment includes: The phosphide product is subjected to nitrogen plasma treatment in a plasma reaction chamber, where the gas flow rate is set to 50 - 100 sccm, the plasma power is 100 - 200 W, and the treatment time is 5 - 10 minutes. The pressure in the reaction chamber is controlled at 10 - 50 Pa, and after the treatment is completed, the catalyst is naturally cooled to room temperature and stored in a sealed manner.
Citation Information
Cited By
High-activity catalyst for producing hydrogen by electrolyzing water as well as preparation method and application of high-activity catalyst
CN120989664A